Factors that influence the adherence of the elderly to antihypertensive therapy (Research, Society and Development, 2021)
Objectives: to search the literature for scientific productions about the factors that influence the adherence of the elderly to antihypertensive therapy; characterize scientific studies considering the variables: author / year of publication; study title; study object and main results; describe the factors that facilitate and hinder the patient's adherence to antihypertensive therapy. Methodology: this is an integrative literature review research using the PICo search strategy. The search for the studies was carried out in the databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Nursing Database ( BDENF). The sample consisted of 10 articles and data collection took place between September and October 2020. Results: the results showed that socioeconomic and cultural factors, such as education, income, age, color, marital status, sex, age, are fundamental for adherence to antihypertensive therapy. Conclusion: the low level of education was considered by most authors as one of the main factors that contribute to non-adherence and consequent abandonment of the elderly to drug treatment. In addition, the simultaneous use of several medications and low income result in inadequate adherence, thus hampering the continuity of the proposed medication regimen.